Adoption of and compliance with IFRS in developing countries: A synthesis of theories and directions for future research. Issue 1 (1st February 2016) - Samaha, Khaled; Khlif, Hichem
Abstract : Purpose: – The purpose of this paper is to review a synthesis of theories and empirical studies dealing with the adoption of and compliance with IFRS in developing countries in an attempt to provide directions for future research. Design/methodology/approach: – The review focusses on four main streams including: first, the motives for IFRS adoption; second, corporate characteristics and the degree of compliance with IFRS; third, the economic consequences of IFRS adoption and finally; fourth, the use of regulation as an enforcement mechanism to monitor compliance with IFRS. The authors review empirical studies specifically devoted to developing countries. Findings: – Regarding the first stream relating to IFRS adoption, the macroeconomic decision of adopting IFRS in developing countries can be justified by two main theories which are: the economic theory of network (Katz and Shapiro, 1985) and isomorphism (DiMaggio and Powell, 1991), however, empirical evidence in developing countries to confirm these theories is limited. Regarding the second stream relating to corporate characteristics and the degree of compliance with IFRS, the authors find that the results are mixed. Regarding the third stream relating to the economic consequences of IFRS adoption, it seems that the evidence is still limited in developing countries especially with respect to the impact of IFRS adoption on foreign direct investment, cost of equity capital and earnings management. Regarding the fourth and final stream in relation to regulation, enforcement and compliance with IFRS, the authors find that research is very limited. It was evidenced in the very few research studies conducted, that global disclosure standards are optimal only if compliance is monitored and enforced by efficient institutions. Practical implications: – The author's study attempts to provide a foundational knowledge resource that will inform practitioners, researchers and regulators in developing countries about the relevance of the different theories that exist in the accounting literature to explain the adoption of and compliance with IFRS. Originality/value: – Compared to developed countries, the four streams outlined remain under-researched in developing countries. Therefore, researchers should examine these topics in developing countries to inform practitioners, regulators and the capital market about the effects of adopting IFRS and their relevance to developing countries. In addition, researchers should embark on identifying new theories to explain the adoption of and compliance with IFRS in developing countries that take into consideration the socioeconomic culture of these settings.